Hifdz al-Qur’ân Bi ad-Dimâghi al-Yumnâ Bi Ma’had La Raib Hanifida, Jombang - Ilham Habibullah; Abdul Malik (Universitas Darussalam Gontor, 2018)
Basically, there are many moslems who memorize Qur'an in sequence from beginning to end. This methods is called conventional methods that need left brain ability. On the other hand, the method of memorizing the Qur'an with the right brain ability the contemporary method, this method has lots of results such as verse, translation, memorization from front to back or vice versa and random. This paper aims to find out the method thas use to memorize the Qur'an by right brain. The conclusion from this study is in memorizing Qur'an there is (Brain Based Learning). This method is highly optimize the right brain activity by applying 5 methods as follows: 1) method of story. 2) method of replacement. 3) method of location. 4) method of number. 5) method of sentence.